Nutritional and Nanotechnological Modulators of Microglia - Maysinger, Dusica; Zhang, Issan (Frontiers in Immunology, 2016)
Microglia are the essential responders to alimentary, pharmacological and nanotechnological immunomodulators. These neural cells play multiple roles as surveyors, sculptors, and guardians of essential parts of complex neural circuitries. Microglia can play dual roles in the central nervous system; they can be deleterious and/or protective. The immunomodulatory effects of alimentary components, gut microbiota and nanotechnological products have been investigated in microglia at the single cell level and in vivo using intravital imaging approaches, and different biochemical assays. This review highlights some of the emerging questions and topics from studies involving alimentation, microbiota, nanotechnological products, and associated problems in this area of research. Some of the advantages and limitations of in vitro and in vivo models used to study the neuromodulatory effects of these factors, as well as the merits and pitfalls of intravital imaging modalities employed are presented.